Propaganda and Political Memes on Social Media in the 2019 Indonesian Presidential Election - Akhirul Aminulloh; Fathul Qorib; Latif Fianto; Emei Dwinanarhati Setiamandani (Journal of Islamic World and Politics, 2022)
Political memes colored the 2019 Indonesian presidential election campaign on social media. Political memes have become one of the propaganda strategies to influence public opinion to gain political support from the public before the presidential election. This study aims to analyze and understand political memes as a medium of political propaganda in the 2019 Indonesian presidential election. This study uses critical discourse analysis to uncover the meaning behind the text. The data collection technique uses documentation in the form of political memes of the two presidential candidates, both in images and political symbols scattered on social media in the January – March 2019 period. Furthermore, the data will be analyzed using Fairclough's critical discourse analysis model to find out the meaning of the text. This study indicates that social media plays an essential role in political communication in the 2019 presidential election campaign. Social media is a cheap and fast means of spreading political memes that reach potential voters widely and massively. Through political memes, Joko Widodo often talks about having links with the Indonesian Communist Party. Meanwhile, Prabowo Subianto is often spoken of by his political opponents as a supporter of the caliphate in Indonesia. These political memes are used as political propaganda to construct or deconstruct political presidential candidates' discourse and build or damage the reputation of presidential candidates to influence public opinion.